Improving sport spaces into urban areas for healthy and inclusive communities: the case of Milan. (20th October 2021) - Gola, M; Buffoli, M; Rebecchi, A; Fior, M; Daprà, F; Vettori, MP; Capolongo, S
Abstract: Background: Cities are health promoters, although many of them lack of spaces for sport practice. In the meanwhile, for instance, several recreational and sport spaces, that can be open to the community, are offered by the network of churches. A research is developing a tool for making more efficient the assets of sport activities in parishes in a multi-generational, inclusive and health education perspective, in response to increasingly evident needs related to social and sports demand, education health, enhancement of the built heritage and social inclusion. The social and technical value based tool merges several issues related to Public Health, Urban Health, sport facilities design, urbanism and social impact. Methods: The first part of the tool refers to an urban analysis of the city to be investigated and it highlights the correlations among the parishes, sport infrastructures, population density and social inequalities, physical activity and green areas. All the analysis refer to the GIS systems in which all the data are collected and organized by districts. Results: The application was done in the city of Milan (Italy). The analysis with GIS system gives rise to several maps (a-population health status with a focus on physical activity, b-sport infrastructures availability, c-parishes available, etc.) with different results and they have been merged together. Some areas show some critical aspects related to the lack of public sport spaces, green areas and social inequalities. It permits to select the case studies to be taken in consideration for the application of the Strategic Design Framework, and it will allow to give rise to a detailed examination of the parishes' potentialities for improving the sport practice. Conclusions: The tool is working progress and it will be validated through the application on 5 case studies in the city of Milan. The research is funded by Politecnico di Milano - PoliSocial Award 2019, entitled "SPèS" (Sport is Society). Key messages: Social governance, health promotion and urban inclusion, through the reactivation system of the sport infrastructures in the parishes of Milan. Local parishes as health promoters of sport practice: sport infrastructures for the local communities in Milan.